Statistics of Scientific Procedures on Living Animals Great Britain 2015 — Highlighting an Ongoing Upward Trend in Animal Use and Missed Opportunities for Reduction. Issue 6 (December 2016) - Hudson-Shore, Michelle
The Annual Statistics of Scientific Procedures on Living Animals Great Britain 2015 indicate that the Home Office were correct in recommending that caution should be exercised when interpreting the 2014 data as an apparent decline in animal experiments. The 2015 report shows that, as the changes to the format of the annual statistics have become more familiar and less problematic, there has been a re-emergence of the upward trend in animal research and testing in Great Britain. The 2015 statistics report an increase in animal procedures (up to 4, 142, 631) and in the number of animals used (up to 4, 069, 349). This represents 1% more than the totals in 2013, and a 7% increase on the procedures reported in 2014. This paper details an analysis of these most recent statistics, providing information on overall animal use and highlighting specific issues associated with genetically-altered animals, dogs and primates. It also reflects on areas of the new format that have previously been highlighted as being problematic, and concludes with a discussion about the use of animals in regulatory research and testing, and how there are significant missed opportunities for replacing some of the animal-based tests in this area.